2001
DOI: 10.1016/s0039-6257(00)00196-x
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation Syndrome

Abstract: Exfoliation syndrome (XFS) is an age-related disease in which abnormal fibrillar extracellular material is produced and accumulates in many ocular tissues. Its ocular manifestations involve all of the structures of the anterior segment, as well as conjunctiva and orbital structures. Glaucoma occurs more commonly in eyes with XFS than in those without it; in fact, XFS has recently been recognized as the most common identifiable cause of glaucoma. Patients with XFS are also predisposed to develop angle-closure g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
626
4
97

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 755 publications
(737 citation statements)
references
References 465 publications
10
626
4
97
Order By: Relevance
“…Whitish fibrillogranular material is visible by slit-lamp microscopy on the anterior lens capsule and at the pupillary border. 2 Furthermore PEX is one of the most common causes of open-angle glaucoma accounting for about 25% of all open-angle glaucoma worldwide. 2 The etiology of PEX syndrome is still poorly understood but increased prevalence of the disease in certain populations and observed familial aggregation are compatible with PEX being a complex genetic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Whitish fibrillogranular material is visible by slit-lamp microscopy on the anterior lens capsule and at the pupillary border. 2 Furthermore PEX is one of the most common causes of open-angle glaucoma accounting for about 25% of all open-angle glaucoma worldwide. 2 The etiology of PEX syndrome is still poorly understood but increased prevalence of the disease in certain populations and observed familial aggregation are compatible with PEX being a complex genetic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…IOL decentration has also been reported even when the lens is entirely in the capsular bag, primarily due to decentration of the entire bag. [19], [20] In our series 1 case had decentration due to zonular dialysis where CTR was not put and a 3 piece IOL was put in the bag. This study demonstrated an increased incidence of intraoperative and post-operative complications.…”
Section: Discussionmentioning
confidence: 70%
“…Marfan's syndrome), trauma or even pseudoexfoliation, can also predispose to angle-closure in a previously deep anterior chamber. (Ritch & Schlötzer-Schrehardt, 2001;Dureau, 2008). Secondary causes of angle-closure, such as phacomorphic, uveitic and neovascular cases, need to be promptly identified in order to establish a specific treatment.…”
Section: Mechanisms Of Angle-closurementioning
confidence: 99%
“…(George et al, 2003;Thomas et al, 2004) Some zonular diseases may be related to secondary angle-closure glaucomas, such as exfoliation syndrome, Marfan´s Syndrome and Weil-Marchesani Syndrome, among others. (Ritch & Schlötzer-Schrehardt, 2001;Dureau, 2008) 7.3 Genetic and other external factors Similarities in ocular biometry in first-degree relatives of angle-closure patients, indicates that angle-closure related anatomical characteristics are at least partially heritable. The risk of developing angle-closure glaucoma was reported to be 3.5 times higher in first degree relatives of affected Inuit patients.…”
mentioning
confidence: 99%